The Moderating Role Of Compensation On The Relationship Between Work Ethic And Job Outcomes - Sjahruddin, Herman (Cita konsultindo, 2025)
Job outcomes are the results or consequences of the work completed by employees. This research positions that the better the work ethic and with a proportional strengthening of compensation, the job outcomes produced by employees are improved. Compensation acts as a moderator because it represents management’s concern for employees, manifested through the provision of compensation, thus encouraging employees to put forth all their capabilities to achieve the desired job outcomes. The distribution of this research questionnaire was conducted among 171 employees of PT. XXX in Makassar City as the population and sample, with a response rate of 78.95%, resulting in 135 employees used as the data analysis unit. This study is explanatory research utilizing a partial least squares-based structural equation model (SEM-Pls4). The results of this research provide evidence that good work ethics and compensation provided to employees, even at a low level, can enhance job outcomes when compensation is strengthened.